2018
DOI: 10.1159/000484570
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Alloantibody Screening: Comparative Analysis of Three Different Technologies

Abstract: Background: The detection of irregular antibody is a critical issue in the management of red blood cell transfusion according to the Type & Screen (T&S) practice. In order to implement the T&S procedure at our blood bank, we compared three different automated analyzers based on column agglutination technique (CAT) or solid phase red cell adherence assay (SPACA) methods. Methods: Pre-transfusion antibody screening was performed in 986 patients candidate to elective surgery at low risk for red blood cell transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Inconsistent results were also found by Quillen et al, who reported for automated solid-phase systems non-repeatability for the detection of antibodies to E, Jk a , and Fy a [29]. A recent comparison found unspecified reactions in 7 cases for the solid phase assay compared to 2 for gel card agglutination [12].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Inconsistent results were also found by Quillen et al, who reported for automated solid-phase systems non-repeatability for the detection of antibodies to E, Jk a , and Fy a [29]. A recent comparison found unspecified reactions in 7 cases for the solid phase assay compared to 2 for gel card agglutination [12].…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, decreased sensitivity with differentiation panels that contain only one instead of two antigen-positive cells is plausible. One group recently published similar findings for Kp a , which increases the sensitivity of the test system if included in screening at the cost of having four instead of three cells per sample in the screening [12].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…According to several international guidelines (such as BSH (British Society for Haematology) and CBO ('Centraal Begeleidingsorgaan') [3], the screening cell set must answer to certain requirements such as the inclusion of at least one cell with homozygous expression of the Fy a , Fy b (Duffy antigens), Jk a , Jk b (Kidd antigens), S and s antigens (MNSs antigens) and heterozygous expression for the K (Kell) antigen [4,5]. If the antibody screen is negative, it can be predicted that more than 99% [2,6] of the RBC units electronically matched for ABO groups will be compatible in the crossmatch (XM) test [7]. A positive antibody detection test is followed by the determination of the antibody specificity and the assessment of its clinical significance.…”
Section: Introductionmentioning
confidence: 99%